The Impact Of Learning Skill Training On Improving Self-efficacy For The New College Students In Psychology Department Of UII - Rachmawati, Mira Aliza (Journal of English and Education (JEE), 2008)
The aim of this research is to improve student's self efficacy through learning skill training at Psychology Department of UII. This research assumed that new college students having lower self efficacy. As mentioned by most psychologists, the individuals are expected to be responsible in order to gain optimum achievement from teenager to adulthood. Low self efficacy associates with teaching learning processes for college students. This research had employed experimental -design consisted of one group pretest and posttest. Subjects of this study were 144 new college students from Psychology Department of UII. Aspects of learning skill training measured were independent learner, effective learning, and present skill. This statistical analysis of t-test was used to examine differences between groups. The result shows that learning skill training can improve self efficacy for new college student (i=-2.438; p=0.016).